Dispositivos móviles y su incidencia en los procesos de aprendizaje en los estudiantes de la carrera de Fisioterapia, sección matutina de la Universidad Técnica de Babahoyo, periodo diciembre 2022- abril 2023 - Arechua Sandoya, Adrián Antonio (2023)
The present research work had the purpose of analyzing mobile devices and their incidence in the learning processes of physiotherapy students, morning section of the technical university of Babahoyo, period December 2022- to April 2023. It should be noted that the objective of this research was to determine how the use of mobile devices affects the learning process of physiotherapy students of the morning section of the technical university of Babahoyo. The methodology used in this work is quantitative (mixed) with bibliographic and descriptive type, this research was conducted in the career of Physiotherapy morning section of the Technical University of Babahoyo. We worked with a sample of 112 students, it should be noted that the results were obtained thanks to a survey conducted virtually to the students. Thus, through the processing, analysis and interpretation of data obtained as a result of the research, was that students said that the use of mobile devices is a very important tool for the development of educational activities even for classes to be more interactive and dynamic when teaching them. The research suggests the need for adequate training among teachers and students in order to correctly use the effective and responsible use of mobile devices as an educational tool, it is important to take into account these opinions to establish clear pedagogical strategies so that students are interested in learning and developing their educational skills.